2005
DOI: 10.1007/s11270-005-8265-9
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Impact of Chemical Deicers – A Review

Abstract: Increased application of chemical deicers for winter maintenance has resulted in increased concentrations of deicer constituents in the environment. The runoffs from the deicing operation have a deteriorating effect on soil and water quality. But the degree of impact is localized and it depends on various climatic factors and can also be attributed to the type of salts used and their storage conditions. This paper presents a review of the environmental impact of deicing chemicals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
255
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 412 publications
(258 citation statements)
references
References 35 publications
1
255
0
2
Order By: Relevance
“…low pH levels of forest soils (3.8-4.0 at control points) were increased up to neutral or alkaline values. Several studies also reported that saline soils could have higher pH values (about 7.5-8) mainly due to sodium cation accumulation and consequently higher base saturation (Bouzille et al 2001, Czerniawska-Kusza et al 2004, ramakrishna and viraraghavatan 2005. Soil microbial properties were influenced by different physical-chemical properties but it is not easy to distinguish the effects of parameters changed by salting and the effects of natural soil properties.…”
Section: Resultsmentioning
confidence: 99%
“…low pH levels of forest soils (3.8-4.0 at control points) were increased up to neutral or alkaline values. Several studies also reported that saline soils could have higher pH values (about 7.5-8) mainly due to sodium cation accumulation and consequently higher base saturation (Bouzille et al 2001, Czerniawska-Kusza et al 2004, ramakrishna and viraraghavatan 2005. Soil microbial properties were influenced by different physical-chemical properties but it is not easy to distinguish the effects of parameters changed by salting and the effects of natural soil properties.…”
Section: Resultsmentioning
confidence: 99%
“…Sodium chloride was used as a deicer in the USA as early as in 1950s (Godwin et al 2003), and the first comprehensive environmental impact assessment of highway deicing was published by the US Environmental Protection Agency in 1971(US EPA 1971. Of the chemical deicers, the most popular is sodium chloride (NaCl), but calcium and magnesium chlorides (CaCl 2 , MgCl 2 ) are also widely used (Ramakrishna and Viraraghavan 2005). In the recent years, alternative road deicers have appeared commonly substituting for traditionally used chlorides in order to minimize their negative influence on the environment, building materials and metal corrosion (Robidoux and Delisle 2001;Hellstén et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…A long-term use of sodium chloride for winter road maintenance leads to accumulation of sodium and chloride especially in the urban environment (Godwin et al 2003;Ramakrishna and Viraraghavan 2005;Green et al 2008;Cunningham et al 2008). It should be stressed that all the chemical deicers, regardless of their composition, influence the chemistry of waters, soils, and vegetation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations